Sidewalks and Urban Equipment Modification for Veterans and Disabled Persons - A.R. Abdolahzade fard; S.K. Sorourzadeh; N. Azhdari (Afarand Scholarly Publishing Institute, 2016)
Aims: One of the requirements of every society is the adaptation of urban services and environments with the needs of the veterans and disabled persons. The aim of this study was to investigate satisfaction with the adaptation of the sidewalks and urban equipment on Enghelab Islami Ave. of Shiraz with needs of the veterans and persons with motor disabilities. Instrument & Methods: In the applied descriptive-analytic study, the satisfaction levels of 379 veterans and persons with motor disabilities of Shiraz with the equipment and urban services of Enghelab Islami Ave. were studied in 2015. The subjects were selected by Simple Random sampling method. Data was collected via interviews, observations, and a researcher-made questionnaire. Data was analyzed by SPSS 20 software using descriptive statistics. Findings: On the studied avenue, lack of any planning in the adaptation of urban services and equipment with the physical status of the disabled persons was the major urban equipment problem of the veterans and disabled persons related to the physical barriers on the sidewalks. The levels of satisfaction with the public transportation, urban furniture, adaptation of sidewalk floor, and proper WC were 11.9%, 30.1%, 25.3%, and 22.2%, respectively. In addition, total satisfaction level percentage was 22.2%. Conclusion: Not properly designed, the urban environment and equipment of Enghelab Islami Ave. of Shiraz are not adapted with the needs of the veterans and persons with motor disabilities. The satisfaction level of the conducted adaptations of the avenue is 22.2%.